Host Quality and Interactivity: Consumer Engagement’s Mediation in Shopee Live Purchase Intention among Jabodetabek Consumers - Ronaldo Winarto; Bernard T Widjaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
As consumer purchasing behaviour rapidly shifts toward online channels, live commerce has emerged as a critical marketing strategy, necessitating the investigation of its core purchase drivers. This explanatory study analyzed how host quality and platform interactivity influence consumer purchase intention, utilizing consumer engagement as a mediating psychological mechanism. The research focused on urban Millennial (1981–1996) and Gen Z (1997–2012) users residing in Jabodetabek who utilize the dominant Shopee Live platform. Data were gathered via an online quantitative survey from 166 qualified consumers and analyzed using the Partial Least Squares Structural Equation Modeling (PLS–SEM) method. Findings confirmed that both host quality and interactivity positively and significantly predicted engagement. Notably, interactivity demonstrated a significant direct influence on purchase intent, whereas host quality did not show a direct effect. Consequently, engagement served as a full mediator for the host quality–purchase intention link, and a partial mediator for the interactivity–purchase intention relationship. This validates the Stimulus–Organism–Response (S–O–R) framework, confirming that host attributes and platform features (S) enhance engagement (O), which is the essential bridge driving purchasing behaviour (R). Practically, these results guide e-commerce platforms and merchants to prioritize host training and interactive feature development to maximize engagement-driven conversion.